2008
DOI: 10.1037/0021-843x.117.2.396
|View full text |Cite
|
Sign up to set email alerts
|

Incremental validity of the Psychopathy Checklist facet scores: Predicting release outcome in six samples.

Abstract: The incremental validity of the 4 facet scores (Interpersonal, Affective, Lifestyle, Antisocial) of the Psychopathy Checklist-Revised (PCL-R; R. D. Hare, 1991, 2003) and the Psychopathy Checklist: Screening Version (PCL:SV; S. D. Hart, D. N. Cox, & R. D. Hare, 1995) was evaluated in 6 forensic/correctional samples with average follow-ups ranging from 20 weeks to 10 years. Results indicated that whereas Facet 4 (Antisocial) achieved incremental validity relative to the first 3 facets (Interpersonal, Affective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
153
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(178 citation statements)
references
References 44 publications
20
153
4
1
Order By: Relevance
“…These results are concordant with the findings reported by Kahn, Byrd, and Pardini (2013) and Walters et al, (2008). The two dimensions of psychopathy assessed in this research were: 1) Interpersonal dimension (A-Grandiosity, three items [1A I am surrounded by lots of dumb and stupid people, 2A Only dumb people get robbed, 3A Dumb people deserve to be deceived]; B-Lying, five items[1B It is justified to lie to protect yourself, 2B I enjoy deceiving others, 3B I enjoy lying, 4B Lying is justified in order to get what you want, 5B The best thing I can do is to tell the truth]) and 2) Affective dimension (Lack of empathy, five items): 1-If I do harm to others is because they deserve it, 2-I manipulate other people to get what I want, 3-It is correct to make others suffer if they deserve it, 4-I feel the pain of others in my own flesh, and 5-I reach my goals taking other people into account.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are concordant with the findings reported by Kahn, Byrd, and Pardini (2013) and Walters et al, (2008). The two dimensions of psychopathy assessed in this research were: 1) Interpersonal dimension (A-Grandiosity, three items [1A I am surrounded by lots of dumb and stupid people, 2A Only dumb people get robbed, 3A Dumb people deserve to be deceived]; B-Lying, five items[1B It is justified to lie to protect yourself, 2B I enjoy deceiving others, 3B I enjoy lying, 4B Lying is justified in order to get what you want, 5B The best thing I can do is to tell the truth]) and 2) Affective dimension (Lack of empathy, five items): 1-If I do harm to others is because they deserve it, 2-I manipulate other people to get what I want, 3-It is correct to make others suffer if they deserve it, 4-I feel the pain of others in my own flesh, and 5-I reach my goals taking other people into account.…”
Section: Discussionsupporting
confidence: 83%
“…For instance, Levy (1934), Menaker (1939), Tiebout (1930) and Tiebout and Kirkpatrick (1939) approached theft from a psychoanalytic standpoint while Henderson (1981), Luiselli and Pine (1999), Stumphauzer (1976) and Wetzel (1966) used behavioral techniques in an attempt to find ways to reduce it in specific cases, achieving encouraging results. Much research has also been done and several models have been developed on theft and, in general, on antiproductive work behavior, taking into account different personality characteristics (Berry, Ones, & Sackett, 2007;Mount, Ilies, & Johnson, 2006;Mustaine & Tewksbury, 2002;Spector, 2011;Spector & Fox, 2005); to date, few studies have investigated the predictive power of the affective dimension (e.g., shallow affect, callousness, and lack of empathy/remorse) and the interpersonal dimension (e.g., grandiosity, lying) of psychopathy on future criminal behavior and, in particular, on theft (Kahn, Byrd, & Pardini, 2013;Walters, Knight, Grann, & Dahle, 2008).…”
mentioning
confidence: 99%
“…A meta-analysis involving 15,826 individuals indicated that the PCL-R had a moderate effect size in predicting interpersonal violence [33]. Another meta-analysis showed a similar result [34].…”
Section: Comorbidity Of Schizophrenia and Psychopathy/antisocialsupporting
confidence: 53%
“…In essence, the key and now long standing validity concern of the PCL-R and PCL-YV has been that its key personality dimensions have not been predictive of central measures of criminality. More recently, in a series of studies encompassing ten different samples and nearly 2900 subjects, Walters and colleagues confirmed that the antisocial facet of the PCL consistently predicted general and violent recidivism above and beyond the contributions of the first three facets (interpersonal, affective, and lifestyle), but the first three facets consistently failed to display incremental validity relative to the antisocial facet in predicting these same two outcomes (Walters & Heilbrun, 2010;Walters, Knight, Grann, & Dahle, 2008;Walters, Wilson, & Glover, 2011). Walters (2012) subsequently reported that the first three facets of the PCL-R, which according to the results of factor and IRT analysis constituted the optimal model for PCL-R psychopathy in a group of Canadian offenders, failed to predict general or violent recidivism above and beyond the contributions of age and criminal history.…”
Section: Introductionmentioning
confidence: 87%